2018
DOI: 10.3389/fped.2018.00260
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Febrile Children Presenting to the Emergency Department: A Systematic Review

Abstract: Introduction: While fever is the main complaint among pediatric emergency services and high antibiotic prescription are observed, only a few studies have been published addressing this subject. Therefore this systematic review aims to summarize antibiotic prescriptions in febrile children at the ED and assess its determinants.Methods: We extracted studies published from 2000 to 2017 on antibiotic use in febrile children at the ED from different databases. Author, year, and country of publishing, study design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
(151 reference statements)
1
5
0
Order By: Relevance
“…This is as expected, since the previously reported rates were calculated in relation to the number of inhabitants, whereas our review only considered acutely ill children. This review confirms that heterogeneity is intrinsic to this type of research 9–12. Compared with similar reviews,9–12 this review represents a greater number of countries and healthcare settings.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This is as expected, since the previously reported rates were calculated in relation to the number of inhabitants, whereas our review only considered acutely ill children. This review confirms that heterogeneity is intrinsic to this type of research 9–12. Compared with similar reviews,9–12 this review represents a greater number of countries and healthcare settings.…”
Section: Discussionsupporting
confidence: 69%
“…This review confirms that heterogeneity is intrinsic to this type of research. 9-12 Compared with similar reviews, [9][10][11][12] this review represents a greater number of countries and healthcare settings. Further, we used a more elaborate search strategy.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A literature review on antibiotic prescription rates and their determinants in febrile children in emergency care found large heterogeneity of studied populations, which limited the ability to draw conclusions [16]. One recent European study, focusing solely on EDs, showed significant differences in antibiotic prescription rates in otherwise healthy children with respiratory tract infections (RTIs) [5].…”
Section: Plos Medicinementioning
confidence: 99%
“…Unfortunately, in both hospital and outpatient settings, the prescription of broad-spectrum antibiotics is often inappropriate or unnecessary (e.g., patients with viral infections or noninfectious diseases) in 50% of cases (Hecker et al, 2003). This practice is closely related to the increase in AMR ( van de Voort et al, 2018) and other issues, including the increased incidence of Clostridium difficile infections (Baur et al, 2017). In 2019, Josephine et al carried out a detailed analysis on the variability of prescriptions in certain hospitals (considering a population of children without comorbidities who had received antibiotics) by country, focus of the infection (particularly with respect to the respiratory tract) and type of antibiotic; they noted that differences in patient combination, diagnostic evaluation or hospital characteristics could not justify all the variability of antibiotic prescription, thus suggesting overuse ( van de Maat et al, 2019).…”
Section: Overview On Antibiotic Resistancementioning
confidence: 99%